The Effect Of Tax Avoidance On Firm Value With Tax Expert As Moderating Variables - Nurseto, Ian; Bandiyono, Agus (Jurnal Keuangan dan Perbankan, 2021)
The company's goals in this modern era have undergone significant changes. The company's focus has changed from focusing on maximizing profit to increasing firm value. Firm value, which is reflected in the value of the company's shares, can grow along with the increase in company profits. Tax, which is an element of development, is seen by companies as one of the factors that determine the company's value. This is a consideration for companies to behave in tax avoidance or not. This study tries to analyze the relationship between tax avoidance by the entity and its firm value and the extent to which the tax expert influences both of these. This study provides several conclusions, i.e., tax avoidance has a negative effect on firm value. These results contradict the initial testing hypothesis where tax avoidance has a positive impact on firm value. The moderating influence, tax experts, don't affect the relationship between tax avoidance and firm value.JEL: D13, I31, J22*